The features of process of socialization of personality in conditions of hybrid warfare in Donbas - Savchenko Serhii (Borys Grinchenko Kyiv Metropolitan University, 2017)
The article reveals the features of process of socialization of personality in conditions of hybrid warfare in Donbas;proved ideas for developing the theory of socializationof personality in conditionsof hybrid warfare by updating and clarifying concepts and terminology. The article presents examples of external social and institutional regulators, including: mass media, national and cultural traditions, norms, customs (in our case, false, misleading, distorted, external values, and perceptions of the surrounding world). All this together becomes a regulator of personality behavior. And the more personalities are uncultured, the less attention they devote to their own development, the more they are socially irresponsible and not capable of self-determination, amateur actions and rule-making, and thus more convenient for external manipulation. It is proved that the most well-aimed to determine the negative transformations in the personality as a result of a hybrid warfare in East Ukraine is the concept of «aberrational socialization», which means negative, false socialization of the personality as a result of aggressive and distorted by external influences, and «aberrational activity», the essence of which is the activity of such personality, antisocial aimed at achieving the objectives. The proposed new treatment process of socialization of personality, which is presented as a three-level model, the main components are: the assimilation of social norms, practices, values, roles, relationships, patterns of behavior, etc; playing them through their own activity; creating a new in social environment (the capacity for social innovation).